The law, economics and politics of international standardisation - Delimatsis, Panagiotis; Tilburg Law and Economics Center (Cambridge : Cambridge University Press, 2015)
In an era of increased reliance on private regulatory bodies and globalised economic activity, standardisation is the field where politics, technical expertise and strategic behaviour meet and interact. International standard-setting bodies exemplify the rise of transnational governance and the challenges that it brings about relating to institutional choice, legitimacy, procedural and substantive fairness or transparency. This book takes a more empirical-based approach focusing on the mechanics of international standard-setting. It constitutes a multidisciplinary inquiry into the foundations of international standard-setting, an empirically under-researched yet important area of international informal lawmaking. Contributors expertly examine the peculiarities of international standardisation in selected issue-areas and legal orders and shed light on the attributes of international standard-setters, allowing comparisons among standard-setting bodies with a view to identifying best practices and improve our understanding about standardisation processes.
Introduction: continuity and change in international standardisation / Panagiotis Delimatsis -- Part I. International standard-setting -- a multifaceted and evolving area of research -- 1. Standardisation: a developing field of research / Henk J. De Vries -- 2. ISO standards and authoritative collective action: conceptual and normative issues / Hans Lindahl -- 3. From standards to quality infrastructure: a review of impact studies and an outlook / Knut Blind -- Part II. International standardisation and the World Trade Organization -- 4. Global food safety standards: the evolving regulatory epistemology at the intersection of the SPS Agreement and the Codex Alimentarius Commission / Alessandra Arcuri -- 5. 'Relevant international standards' and 'recognised standardisation bodies' under the TBT Agreement / Panagiotis Delimatsis -- 6. Technical standard-setting in the financial sector / Juan A. Marchetti -- 7. Standardising trade in services? / Petros C. Mavroidis -- Part III. The politics and dynamics of international and regional standardisation -- 8. The power of the penholder: the missing politics in global regulatory governance analysis / Walter Mattli and Jack Seddon -- 9. Between standards and regulation: on the concept of 'de facto mandatory standards' after Tuna II and Fra.bo / Harm Schepel -- 10. Competition and cooperation in the market of voluntary sustainability standards / Axel Marx and Jan Wouters -- 11. Harmonizing non-tariff measures: always a blessing? / Olivier Cadot, Anne-Célia Disdier and Lionel Fontagné -- Part IV. International standardisation and development -- 12. You'd be surprised how much it costs to look this cheap! A case-study of ISO 26000 on social responsibility / Stephanie Bijlmakers and Geert Van Calster -- 13. The development dimension of the Codex Alimentarius standard-setting process / Awilo Ochieng Pernet -- 14. Standards of responsible investment and international investment law
Title from publisher's bibliographic system (viewed on 10 Dec 2015).
Keywords: elektronické knihy; electronic books; Standardization -- Law and legislation -- Congresses